Catalytic approach toward chiral P,N-chelate complexes utilizing the asymmetric hydrophosphination protocol - Katona, Dávid (2021)
A synthetic procedure for obtaining a chiral P,N ligand was developed by exploiting the versatility of the asymmetric hydrophosphination protocol catalyzed by a phosphapalladacycle complex. The addition of the synthesized ligand to various metal sources led to the generation of chiral and enantioenriched chelate complexes, which can be useful prototypes for catalyst design in the future. The resulting coordination compounds were comprehensively characterized by solid-state (X-ray crystallography) and solution-based (one- and two-dimensional NMR spectroscopy) techniques and natural bond orbital (density functional theory) analysis to determine their structural and key electronic features.